Liquid organic manures A boon to organic farmers - Mahanta, Dibakar; Dhar, Shiva (Indian Farming, 2021)
Liquid organic manures have beneficial effect on growth, yield and quality of crops and enhance the shelf life of fruits. It not only enhances the yield of crops, but improves soil quality and enhances the sustainability of organic production system in long run. Liquid and solid organic manure complement each other and hence, the former should not be used as substitute to the later. The use of liquid organic manure should be encouraged to promote low-cost organic farming. This lowcost technology will help in achieving the doubling of farmers’ income due to higher net returns. Liquid organic manure is a great boon for organic growers.